English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I can not figure these out for the life of me .. please help

Solve the equation by completing the square.

-7x^2 - 10x + 3 = 0

x^2 - 3x - 15 = -5

x^2 - 17x = -10x - 6

2007-11-15 15:21:30 · 3 answers · asked by Jaz 'ma' Taz 2 in Science & Mathematics Mathematics

3 answers

x^2 - 3x = 10
x^2 - 3x + (3/2)^2 = 10 + (3/2)^2
(x-(3/2)^2 = 49/4
x-(3/2) = +7/2 or -7/2
x = 3/2 + 7/2 = 5 or -2

x^2 - 7x = -6
x^2 - 7x + (7/2)^2 = -6 + (7/2)^2
(x-(7/2))^2 = -6 + 49/4
(x-(7/2)) ^2 = 25/4
x-(7/2) = +5/2 or -5/2
x = 7/2+5/2 = 6 or 7/2-5/2 = 1

2007-11-15 15:30:43 · answer #1 · answered by norman 7 · 0 0

-7x^2 - 10x + 3 = 0, circulate huge type to easily right -7x^2 - 10x = -3, mult the two factors be -a million or 7x^2 +10x = 3, element-out the 7 or 7(x^2 +10/7 x) = 3, div by making use of seven (x^2 +10/7 x) = 3/7, complete sq. (x^2 +10/7 x + (10/14)^2 ) = 3/7 + (10/14)^2, notice we upload same element to the two factors (x +10/14)^2 = 3/7 + (10/14)^2, sparkling-up in simple terms right facet (x +10/14)^2 = 3/7 + (5/7)^2, sparkling-up some extra (x +10/14)^2 = 3/7 + 35/40 9 (x +10/14)^2 = 21/40 9 + 35/40 9 (x +10/14)^2 = fifty six/40 9, take sqrt, sparkling up left x +10/14 = + - sqrt(fifty six/40 9), sparkling-up left and in simple terms right x + 5/7 = + - sqrt(fifty six)/7 x = (- 5/7) + - sqrt(fifty six)/7 , notice there are 2 solutions.

2016-11-11 19:06:19 · answer #2 · answered by Anonymous · 0 0

You can complete the square or simply use the quadratic formula:

Go to this website to help you out:

http://www.1728.com/quadratc.htm

For each of these, move all the variables and constants to the left and make certain it equals 0.

2007-11-15 15:32:55 · answer #3 · answered by Adam Gaha 2 · 0 0

fedest.com, questions and answers